Opening an Arctic Escape Route: The Bellot Strait Expedition - Lajeunesse, Adam; Lackenbauer, P. Whitney (The Northern Mariner / Le marin du nord, 2021)
During the second half of the 1950s, Canadian and American vessels surged into the North American Arctic to establish military installations and to chart northern waters. This article narrates the expeditions by the eastern and western units of the Bellot Strait hydrographic survey group in 1957, explaining how these “modern explorers” grappled with unpredictable ice conditions, weather, and extreme isolation to chart a usable Northwest Passage for deep-draft ships. The story also serves as a reminder of the enduring history of US Coast Guard and Navy operations in Canada’s Arctic waters in collaboration with their Canadian counterparts. Au cours de la deuxième moitié des années 1950, des navires canadiens et américains ont envahi l’Arctique nord-américain pour y établir des installations militaires et cartographier les eaux du Nord. Le présent article traite des expéditions des unités est et ouest du groupe de levés hydrographiques du détroit de Bellot en 1957 et explique comment ces « explorateurs modernes » ont été confrontés à des états de glace imprévisibles, à des conditions météorologiques et à un isolement extrême en traçant un passage du Nord-Ouest utilisable pour les navires à forts tirants d’eau. Le récit nous rappelle également l’histoire durable des opérations de la Garde côtière et de la Marine américaines dans les eaux arctiques du Canada en collaboration avec leurs homologues canadiens.